Hepatitis B Virus Infection and Immunity - Waters,JA; Foster,GR; Thursz,MR; Thomas,HC (2014)
Hepatitis B virus (HBV) infection is a major public health problem, there being approximately 300 million people infected worldwide, and is a major cause of chronic liver disease and hepatocellular carcinoma. The majority of adults infected have a transient, acute hepatitis from which they completely recover and clear the virus. Infection with HBV in adults usually results in an acute, self-limiting, inflammatory disease. It is likely that there are many different reasons why the chronic carrier state develops after adult infection, and the liver pathology in chronic disease is probably the result of a dynamic equilibrium between the replication of the virus and the host's immune response. HBV is not thought to be directly cytopathic; the liver damage in both the acute and the chronic disease is probably caused by the host immune response. Apoptosis is an active process involving autolysis of cells that are damaged or redundant. One of the crucial issues in HBV infection is identification of the factors which determine the outcome of infection. A number of groups have looked for HBV disease associations with MHC class II, and the results are summarized this chapter. HBsAg vaccines are now in widespread use throughout the world. When these vaccines are used to prevent neonatal transmission from HBeAg-positive infected mothers, the best protection is achieved when given with hyperimmune globulin. Important developments in control of replication by antiviral agents and/or modulation of the immune response are needed, along with improvements in the vaccine and the level of delivery.